Microbiome as a Key Player in Sustainable Agriculture and Human Health - Suman, Jarupula; Rakshit, Amitava; Ogireddy, Siva Devika; Singh, Sonam; Gupta, Chinmay; Chandrakala, J. (Frontiers in Soil Science, 2022)
The aggregate of microorganisms in the soil environment is a microbiome that emerged as a vital component of sustainable agriculture in the recent past. These beneficial microorganisms perform multiple plant growth-promoting activities including fixation, mineralization, solubilization, and mobilization of nutrients, production of siderophores, antagonistic substances, antibiotics, and release of plant growth-promoting substances like auxin and gibberellin hormones mediated by interactions between host plant roots and microbes in the rhizosphere. Numerous plant species forms symbiotic association with microbes and draw the benefit of mineral nutrient supply with the expense of minimal energy and their distribution is governed by nature and the number of root exudates, crop species, and cultivars. On the other hand, micro-organisms with critical roles in the microbiome can be isolated, formulated, and developed as a new biological product called biofertilizers. Agriculturally, important microbes with Fe- and Zn-solubilizing attributes can be used for the biofortification of micronutrients in different cereal crops. Regardless of the approach to be used, innovations with the use of microbiomes represent the future of sustainable agriculture. Probiotic microbes such as Lactobacillus etc., are increasingly being used as dietary supplements in functional food products. Effective utilization of microbiome aid in promoting sustainable agriculture that accomplishes a safe environment which in turn manifest positively on human health.